Domestication theory in action: Indonesian Twitter corpus analysis during distance learning - Nurly Meilinda; Billy K. Sarwono; Ummi Salamah (International Journal of Evaluation and Research in Education (IJERE), 2024)
This research aims at analyzing how COVID-19 discourse in the world of education unfolds in the Indonesian Twittersphere by separating public discourse in transition periods, large-scale social restrictions (PSBB), and imposition of emergency restrictions toward community activities (PPKM) and PPKM level 1 to 4. This research used qualitative approach and employed the Domestication Theory to provide a deeper understanding of how individuals integrate technology into their everyday lives. The dataset consisting of 3,196,627 tweets from two keywords and two hashtags was collected and analyzed using corpus linguistics techniques. This study found the emergence of the five main theme groups suggests that users have tried to make sense of and adapt to this new digital learning environment, while also expressing their frustrations and concerns. This highlights the importance of understanding how users domesticate technology and incorporate it into their social and cultural practices. The practical implications of this research include the need to address not only the technical aspects of online learning but also the psychological and social well-being of students, as they navigate this new learning environment.